Герпетофауна северной части Кавказского государственного заповедника - Орлова, В.Ф. (Вестник зоологии, 1973)
In the northern part of the Caucasus state reservation 8 species of amphibians and 10 species of reptiles were found. The places of findings of Caucasian mud-divers, which was previously known only in Transcaucasia, are reported. The data are given on distri¬bution of the found species of amphibians and reptiles within the boundaries of the reser¬vation and by vertical. Some species: Lacerta praticola pontica Lan t z. et C y r e n, L. derjugini N i k., Vipera kaznakovi N i k. are characterized ecologically.